The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/jcm9092825
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Health-Related Quality of Life in Patients with Systolic Heart Failure: Results of the VIDA Multicenter Study

Abstract: Previous studies have shown that heart failure is associated with worse health-related quality of life (HRQoL). The existence of differences according to gender remains controversial. We studied 1028 consecutive outpatients with heart failure and reduced ejection fraction (HFrEF) from a multicentre cross-sectional descriptive study across Spain that assessed HRQoL using two questionnaires (KCCQ, Kansas City Cardiomyopathy Questionnaire; and EQ-5D, EuroQoL 5 dimensions). The primary objective of the study was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 35 publications
5
24
2
Order By: Relevance
“…Women report higher symptom frequency, symptom burden, physical limitations and social limitations, as well as lower QoL. These differences do not appear to be mediated by clinical or biological factors (such as age, body mass index, systolic blood pressure) classically associated with HRQoL nor with HF severity ( 17 , 27 , 36 38 ).…”
Section: Quality Of Life Of People Living With Heart Failurementioning
confidence: 85%
“…Women report higher symptom frequency, symptom burden, physical limitations and social limitations, as well as lower QoL. These differences do not appear to be mediated by clinical or biological factors (such as age, body mass index, systolic blood pressure) classically associated with HRQoL nor with HF severity ( 17 , 27 , 36 38 ).…”
Section: Quality Of Life Of People Living With Heart Failurementioning
confidence: 85%
“…In heart failure, differences between the sexes in health-related quality of life and health status are controversial. While results of many studies have been heterogeneous, some have reported lower KCCQ scores in female than in male heart failure patients, independently from other clinical factors [ 11 , 13 ]. The reason for lower proportions of women in ICD cohorts is unclear, females with primary prevention ICD has been shown to have a lower mortality and lower risk of appropriate therapy than males [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Broadening the picture, gender-specific differences have been emphasized for conceptualizations of patients' presenting difficulties, treatment plans, and mental and medical healthcare pathways [34][35][36][37]. Overall, available evidence suggests that women tend to report higher HRQoL impairments in the context of psychological [38][39][40] or medical difficulties [41,42]. For chronic tinnitus, similar patterns emerged with women describing higher levels of emotional tension, psychological distress, and functional impairment [43][44][45][46], although these findings remain inconclusive [47,48].…”
Section: Introductionmentioning
confidence: 99%